Quantitative study of the effects of early standardized ambulation on sleep quality in patients after hepatectomy - Ni, Chun-yan; Hou, Guo-jun; Tang, Ya-yuan; Wang, Jing-jing; Chen, Wen-jun; Yang, Yuan; Wang, Zhi-hong; Zhou, Wei-ping (Frontiers in Surgery, 2022)
Background：Surgeons are pursuing early functional recovery after oncologic resection. This study aimed to investigate the effects of early ambulation on sleep quality in patients after liver resection via a quantitative study. Methods：A total of 120 patients with hepatic tumors who underwent liver resection were randomly divided into two groups. PSQI was used to score and compare the physical activities and sleep quality. Results：Compared with the control group, patients who started early ambulation after liver resection had significantly better sleep quality, faster recovery of gastrointestinal function and shorter lengths of postoperative hospital stay. No statistical difference was observed in the incidence of postoperative complications between the groups. Conclusion：Early standardized physical activities are feasible for patients after liver resection. They can significantly increase the patient’s sleep duration and improve the sleep quality to reduce the patient’s pain, the nursing workload and achieve rapid recovery.